2019
DOI: 10.3390/molecules24081502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Host Concentration on the Supramolecular Enantiodifferentiating [4 + 4] Photodimerization of 2-Anthracenecarboxylate through Triplet-Triplet Annihilation Catalyzed by Pt-Modified Cyclodextrins

Abstract: Visible-light-driven photocatalytic supramolecular enantiodifferentiating dimerization of 2-anthracenecarboxylic acid (AC) through triplet-triplet annihilation (TTA), mediated by the Schiff base Pt(II) complex (Pt-1, Pt-2, and Pt-3) was studied. The host concentration and the temperature effects on the stereoselectivity were comprehensively investigated. Increasing the concentration of sensitizers/hosts significantly enhanced the conversion of the photoreaction but led to reduced enantioselectivities of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In addition, as can be seen from Table 2, lowering the temperature can significantly enhance the enantioselectivity of the photoreaction, especially at the higher salt concentration. This suggests that the lower temperature can force closer packing of the AC pair included in the CD cavity to energetically and entropically better differentiate the diastereomeric precursor complexes [4i,21] …”
Section: Resultsmentioning
confidence: 99%
“…In addition, as can be seen from Table 2, lowering the temperature can significantly enhance the enantioselectivity of the photoreaction, especially at the higher salt concentration. This suggests that the lower temperature can force closer packing of the AC pair included in the CD cavity to energetically and entropically better differentiate the diastereomeric precursor complexes [4i,21] …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, they used complex 142 b-βCD in a similar study but inconsistent results with low enantioselectivites were found, caused by low water solubility resulting in aggregation. [237] Consequently, complex 142 a-γCD was tested using both laser (523 nm) and LED irradiation (365 nm) including a temperature dependence study (Table 37). Photodimerization induced by 142 a-γCD under LED irradiation did not result in any significant change in product distribution (entries 1-4).…”
Section: Additional Transformationsmentioning
confidence: 99%
“…Furthermore, different isomers of the dimer can be formed [9,22,23]. Therefore, the regio-and enantioselectivity of anthracene photodimerization has been investigated comprehensively, both via experiment and quantum chemistry calculations [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%